Africa 2050: Realizing the Continent's Full Potential. (September 2013) - Ahlers, Theodore; Kohli, Harinder S.; Sood, Anil
This article offers a vision of what Africa could be in 2050. In such a scenario, average per capita income would increase six-fold, an additional 1.4 billion Africans would join the middleclass, the number of poor would shrink to fewer than 50 million, and Africa's share of global gross domestic product (GDP) would triple. For people, the biggest change would be better, less vulnerable jobs with higher productivity; for economies, dramatic productivity increases driven by private sector investment, diversification, and more competition; and for the continent, better integrated sub-regions and relations with the world based on trade and investment rather than aid. In the face of a multi-polar global economy, aging and population growth, increased competition for natural resources, rapid innovation, climate change, urbanization, and natural resource wealth, Africa needs to manage the risk of fragility and conflict, inequality, and the middle-income trap to achieve such a vision.